An education in malice ebook - Gibson, S. T. (2024)
Sumptuous and addictive,  An Education in Malice  is a dark academia tale of blood, secrets and insatiable hungers from S.T. Gibson, author of the cult hit  A Dowry of Blood .  Deep in the forgotten hills of Massachusetts stands Saint Perpetua’s College. Isolated and ancient, it is not a place for timid girls. Here, secrets are currency, ambition is lifeblood, and strange ceremonies welcome students into the fold.   On her first day of class, Laura Sheridan is thrust into an intense academic rivalry with the beautiful and enigmatic Carmilla. Together, they are drawn into the confidence of their demanding poetry professor, De Lafontaine, who holds her own dark obsession with Carmilla.   But as their rivalry blossoms into something far more delicious, Laura must confront her own strange hungers. Tangled in a sinister game of politics, bloodthirsty professors and magic, Laura and Carmilla must decide how much they are willing to sacrifice in their ruthless pursuit of knowledge.   For more from S.T. Gibson, check out  A Dowry of Blood.